الموسيقى في عصر النهضة - الملاحيد. بشير منصور (Aljameai, 2025)
المستخلص: يتناول هذا البحث الموسيقى في عصر النهضة كونها إحدى الظواهر الفنية والثقافية التي شكَّلت ملامح الموسيقى الأوروبية، وأرست العديد من القواعد التي استندت عليها موسيقى العصور اللاحقة. واعتمد البحث على المنهج التاريخي لتتبع مسار تطور الموسيقى ضمن سياقاتها الدينية والدنيوية، وكذلك المنهج التحليلي للكشف عن السمات الفنية والثقافية والفلسفية التي ميزت الموسيقى في هذا العصر. وأظهرت الدراسة العديد من النتائج أهمها أن موسيقى عصر النهضة تميزت بتعدد الأصوات، والتوسع في تركيبة الأكوردات، وظهور الأسلوب التعبيري. Abstract: This research examines Renaissance music as one of the artistic and cultural phenomena that shaped the features of European music and laid down many of the foundations upon which the music of later eras was built. The research adopts the historical method to trace the development of music within its religious and secular contexts, as well as the analytical method to reveal the artistic, cultural, and philosophical characteristics that distinguished the music of this period. The study revealed several findings, the most important of which are that Renaissance music was characterized by polyphony, the expansion of chordal structures, and the emergence of the expressive style.